Ambush Marketing: Blessing Or Curse - Chawla, Nitish (Gyan Management Journal, 2020)
The article gives an insight into the marketing of ambushes; this type of marketing has a different aspect to the marketing strategies used by companies. It is commonly used for companies facing a high degree of competition. The accompanying report presents readers with extensive details on the methods used, forms of ambush marketing, their evolution, various viewpoints on their usage, laws and regulations, and ethical beliefs and expectations. The article also gives examples of the ambush marketing and its effects, pros and cons by companies. Events around the world may have led to laws concerning ambush marketing, but in India, despite a number of activities in ambush marketing in India, there is no specific law dealing with ambush marketing. The article focuses on embassy tactics, the effect of these actions on sponsors, event managers and consumers as well as regulations to discourage such practices.